2020
DOI: 10.5433/2318-9223.2020v8n2p16
|View full text |Cite
|
Sign up to set email alerts
|

Evidenciação dos stakeholders nos GRI’s das empresas presentes no Índice de Sustentabilidade Empresarial (ISE) da B3

Abstract: Este estudo objetivou evidenciar e analisar os stakeholders presentes nos relatórios de sustentabilidade das empresas citadas no índice de sustentabilidade empresarial (ISE) da B3. Para tanto, realizou-se um estudo documental por meio da análise dos relatórios de sustentabilidade das 25 empresas do ISE que estavam em concordância com os critérios da pesquisa. Com base nos dados obtidos neste estudo, percebe-se que os stakeholders mais relevantes são os clientes, acionistas e fornecedores, podendo afetar as org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The independent assessment of the sustainability report presented the percentage of 15% in the same period. Lugoboni et al (2013), argues that the advantages of the independent assessment may include: identification and management of key risks, support in the improvement of performance and value creation, data reliability and its use for decision taking, higher brand appreciation, attractive to customers, competitiveness and market reference.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The independent assessment of the sustainability report presented the percentage of 15% in the same period. Lugoboni et al (2013), argues that the advantages of the independent assessment may include: identification and management of key risks, support in the improvement of performance and value creation, data reliability and its use for decision taking, higher brand appreciation, attractive to customers, competitiveness and market reference.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 99%
“…At the present moment, sustainability continues to be a widely discussed topic and a lot has been argued on its importance, as well as the impact of sustainability practices on the organizational scenario (Lugoboni et al, 2013). In view of the authors Schmitt et al (2013), aiming at the future, we found the beginning of a recognition of the importance in assuming the idea of sustainability, in any management program or activity.…”
Section: Sustainabilitymentioning
confidence: 90%
See 2 more Smart Citations